Crisis and Critique: Philosophical Analysis and Current Events Proceedings of the 42nd International Ludwig Wittgenstein Symposium - Amesbury, Richard 1972-; Birnbacher, Dieter 1946-; Bratu, Christine; Chennoufi, Ridha; Crary, Alice; Engelen, Eva-Maria; Frank, Ulrich; Frick, Marie-Luisa; Gardiner, Stephen M.; Graness, Anke; Haslanger, Sally 1955-; Holzleithner, Elisabeth; et al. (De Gruyter, 2021)
Contemporary deep-reaching changes - whether in financial or real economy, in Europe's political conditions, in the context of scientific theories, in the field of global (environmental) security, or gender relations - are also a challenge to philosophy. The volume comprises cutting-edge scholarly articles from renowned philosophers with various geographical backgrounds and from different philosophical strands. Next to investigating general questions as to the relation of philosophy and critique (What is philosophical critique and which philosophical concepts of critique are of importance today? Where do we need it most? Where are its limits?), the articles focus on issues like theories of democracy and modes of election; the roles of emotions in the political realm; challenges from a widespread discontent in society to politics and science; changes to social identities and different theoretical approaches to social identity formation. The book is indispensable for all who are interested in what contemporary philosophy has to say on crucial issues of our time
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mai 2021)
Keywords: Wittgenstein, Ludwig -- 1889-1951; Kritik; Sozialer Wandel; Wittgenstein, Ludwig; Umweltethik; Entwicklung; Gesellschaft; Politische Philosophie; Philosophie; Gesellschaftskritik; Konferenzschrift -- 2019 -- Kirchberg am Wechsel